2020
DOI: 10.1007/s40430-019-2155-3
|View full text |Cite
|
Sign up to set email alerts
|

Experimental studies of Regulated Metal Deposition (RMD™) on ASTM A387 (11) steel: study of parametric influence and welding performance optimization

Abstract: The present study aims to highlight the effect of the governing variables in regulated metal deposition (RMD™) on the mechanical properties and weld quality of low alloy steel. Current, voltage, and gas flow rate have been considered as main (RMD™) parameters, whereas heat-affected zone, depth of penetration, bead width, and bead height have been taken into account as welding performance characteristics. Signal to noise has been utilized in order to determine the optimal welding parameters, while analysis conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…However, in one of the studies by Das et al [29] it was reported that the weldment prepared by depositing the root passes of the regulated metal deposition (RMD) process and filler passes with the GMAW process using metal-cored wires imparted excellent results. RMD is a modified short-circuit process favorable for root passes for mid-thickness plates (10-25 mm) [30][31][32][33]. From the summary above it is evident that the metal-cored wires enhance the productivity of the process and can be considered for welding of 2.25 Cr-1.0 Mo steels.…”
Section: Introductionmentioning
confidence: 99%
“…However, in one of the studies by Das et al [29] it was reported that the weldment prepared by depositing the root passes of the regulated metal deposition (RMD) process and filler passes with the GMAW process using metal-cored wires imparted excellent results. RMD is a modified short-circuit process favorable for root passes for mid-thickness plates (10-25 mm) [30][31][32][33]. From the summary above it is evident that the metal-cored wires enhance the productivity of the process and can be considered for welding of 2.25 Cr-1.0 Mo steels.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, tacking was performed among both workpieces at a spacing of 03 mm ( Figure 3 b). These workpieces were then fastened for executing welding operation by means of the “Continuum 500” welding machine at obtained optimal settings [ 30 , 31 , 32 ]. The particulars of the welding settings are presented in Table 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, few scholars have optimized the welding operation prior to deploying it in practical uses, yet simply limited endeavors have been undertaken to utilize the RMD technique for low alloy steel. The scholars of this study [ 30 , 31 , 32 ] conducted a number of investigations with a viewpoint of determining the ideal welding conditions for low alloy steel concerning the bead geometry. Current (A) = 100 A, voltage (V) = 13 V, and gas flow rate (GFR) = 21 L/min were the optimal values.…”
Section: Introductionmentioning
confidence: 99%
“…High-quality weld consumables are vital in tool repair since welds in tool applications need to have different properties such as hardness, toughness, wear resistance, temper resistance, heat-checking resistance, and oxidation [2]. Manufacturers often select three types of consumables in arc welding processes [5,[17][18][19]: solid filler wire, flux-cored filler wire, and metal-cored filler wire. Metal-cored filler wire (MCFW) is relatively new to the welding industry and is more helpful in terms of quality and productivity, as well as being ecologically benign [17].…”
Section: Introductionmentioning
confidence: 99%
“…Metal-cored filler wire (MCFW) is relatively new to the welding industry and is more helpful in terms of quality and productivity, as well as being ecologically benign [17]. These filler wires are supplied in diameters in the range of 0.9-2.4 mm and employ Ar (>75%) + CO2 shielding gas combination [5,17,18]. According to Din Bandhu et al [17], MCFW brings together the strengths of solid and flux-cored filler wires, i.e., it combines the fast deposition speed of a flux-cored filler wire with the superior performance of a solid filler wire.…”
Section: Introductionmentioning
confidence: 99%